Manufacturing method of recycled pulp fiber
Patent Information
- Application Number
- JP2022030434
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-02-28
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-02-28
AI Technical Summary
Existing methods for decomposing superabsorbent polymers in recycled pulp fibers using ozone water lead to oxidation changes in the properties of pulp fibers, such as degree of polymerization, carboxyl group content, and alkali dissolution rate, making it difficult to form high-quality recycled pulp fibers.
A method involving the use of both an oxidizing agent and ultraviolet rays to decompose superabsorbent polymers in an aqueous solution, allowing for the formation of recycled pulp fibers with controlled properties by adjusting the ratio of these agents to suit specific applications.
This method effectively reduces the presence of superabsorbent polymer residues and minimizes changes in pulp fiber properties, enabling the production of recycled pulp fibers with predetermined characteristics suitable for various applications.
Abstract
Description
[Technical Field]
[0001] This disclosure relates to a method for producing recycled pulp fibers from a mixture containing pulp fibers obtained from sanitary products and a superabsorbent polymer. [Background technology]
[0002] There are plans to recover recycled pulp fibers from used hygiene products. For example, Patent Document 1 describes a method for recovering pulp fibers from used sanitary products containing pulp fibers and a polymer absorbent, the method comprising the steps of: immersing the used sanitary products in ozonated water to decompose the polymer absorbent; discharging the ozonated water containing the decomposed polymer absorbent to obtain a residue of the sanitary products from which the polymer absorbent has been removed; and washing the residue of the sanitary products from which the polymer absorbent has been removed by stirring it in an aqueous solution containing a disinfectant or in water, thereby decomposing the residue of the sanitary products into its constituent elements. [Prior art documents] [Patent Documents]
[0003] [Patent Document 1] Japanese Patent Publication No. 2014-217835 [Overview of the project] [Problems that the invention aims to solve]
[0004] The inventors have confirmed that when using ozonated water to decompose a polymer absorbent (especially when using an acidic aqueous solution to inactivate the polymer absorbent), it is necessary to expose the pulp fibers to the oxidizing agent for a long time in order to oxidize and decompose the superabsorbent polymer. As a result, the degree of polymerization, carboxyl group content, alkali solubility, etc. of the recycled pulp fibers formed tend to change.
[0005] Therefore, the present disclosure aims to provide a method for forming recycled pulp fibers in which superabsorbent polymers and their residues are less likely to remain, and in which the properties are less likely to change compared to the case in which superabsorbent polymers are oxidized and decomposed using only an oxidizing agent. [Means for solving the problem]
[0006] The Disclosers have found a method for producing recycled pulp fibers from a mixture containing pulp fibers and a superabsorbent polymer obtained from sanitary products, comprising: a recycled pulp fiber formation step in which an oxidizing agent and ultraviolet light are supplied to an aqueous solution containing the mixture to oxidatively decompose the superabsorbent polymer, dissolve the oxidatively decomposed superabsorbent polymer in the aqueous solution to form recycled pulp fibers; and a recycled pulp fiber recovery step in which the recycled pulp fibers are recovered. [Effects of the Invention]
[0007] The method for producing recycled pulp fibers from a mixture containing pulp fibers and a superabsorbent polymer obtained from sanitary products, as disclosed herein, is capable of forming recycled pulp fibers in which the superabsorbent polymer and its residues are less likely to remain, and whose properties are less likely to change compared to the case in which the superabsorbent polymer is oxidized and decomposed using only an oxidizing agent. [Modes for carrying out the invention]
[0008] Specifically, this disclosure relates to the following aspects: [Aspect 1] A method for producing recycled pulp fibers from a mixture containing pulp fibers obtained from sanitary products and a superabsorbent polymer, A recycled pulp fiber forming step involves supplying an oxidizing agent and ultraviolet light to an aqueous solution containing the above mixture to oxidize and decompose the superabsorbent polymer, dissolving the oxidized superabsorbent polymer in the aqueous solution, and forming the recycled pulp fibers. A recycled pulp fiber recovery step in which the above recycled pulp fibers are recovered, The above method, characterized by including
[0009] The inventor of the present application found that while an oxidizing agent is less affected by the transparency of an aqueous solution and can oxidatively decompose and remove a superabsorbent polymer, in cases where the superabsorbent polymer is dehydrated, etc., in order to oxidatively decompose the superabsorbent polymer, it is necessary to expose pulp fibers to the oxidizing agent for a long time. As a result, the degree of polymerization, the amount of carboxyl groups, the alkali solubility rate, etc. of the recycled pulp fibers formed are likely to change.
[0010] In addition, the inventor of the present application found that while ultraviolet rays are affected by the transparency of an aqueous solution, they can oxidatively decompose and remove a superabsorbent polymer, and on the other hand, it is difficult to change the properties of the recycled pulp fibers formed.
[0011] In the above method, since an oxidizing agent and ultraviolet rays are used in combination to oxidatively decompose a superabsorbent polymer, it is difficult for the superabsorbent polymer to remain in the aqueous solution, and thus it is difficult for the recycled pulp fibers formed to contain the superabsorbent polymer and its remains. Also, compared with the case of oxidatively decomposing a superabsorbent polymer using only an oxidizing agent, the change in the properties of the recycled pulp fibers is small.
[0012] [Aspect 2] The method according to aspect 1, wherein the above oxidizing agent is ozone. In the above method, since the oxidizing agent is ozone, the effect of aspect 1 is high.
[0013] [Aspect 3] The above recycled pulp fibers have predetermined properties according to the application, In the above recycled pulp fiber forming step, by adjusting the ratio of ultraviolet rays and an oxidizing agent and supplying them to the above aqueous solution, recycled pulp fibers having predetermined properties according to the application are formed. The method according to aspect 1 or 2.
[0014] In the above method, in the recycled pulp fiber forming step, the ratio of an oxidizing agent to ultraviolet rays is adjusted and supplied to an aqueous solution in a mixture containing pulp fibers and a superabsorbent polymer, so that recycled pulp fibers having predetermined properties according to the intended use can be formed. Therefore, the formed recycled pulp fibers have appropriate predetermined properties according to the intended use and are useful for the intended use.
[0015] [Aspect 4] The method according to aspect 3, wherein the above use is for a cellulose raw material. In the above method, the above use is for a cellulose raw material, and recycled pulp fibers useful as a cellulose raw material can be formed.
[0016] [Aspect 5] The method according to aspect 4, wherein the above cellulose raw material use is selected from the group consisting of cellulose nanofibers, viscose rayon, cellulose derivatives, bioethanol, biobutanol, molding materials, and paper processed products.
[0017] In the above method, the above use is selected from a predetermined group, and recycled pulp fibers useful for a use selected from the predetermined group can be formed.
[0018] [Aspect 6] The method according to any one of aspects 3 to 5, wherein the recycled pulp fibers having the above predetermined properties have a carboxyl group amount of 0 to 0.075 mmol / g.
[0019] In the above method, recycled pulp fibers having a carboxyl group amount within a specific range can be formed. Therefore, the above method can produce recycled pulp fibers suitable for uses where the generation of carboxyl groups is not preferable, such as raw materials for cellulose derivatives such as acetate, rayon raw materials, cellophane raw materials, etc.
[0020] [Aspect 7] The method according to any one of embodiments 3 to 6, wherein the recycled pulp fibers having the above-mentioned predetermined characteristics have an increase in carboxyl groups of 0 to 0.035 mmol / g based on the above-mentioned pulp fibers.
[0021] The above method makes it possible to form recycled pulp fibers having a specific range of carboxyl group content based on pulp fibers. Therefore, the above method can produce recycled pulp fibers suitable for applications where the formation of carboxyl groups is undesirable.
[0022] [Aspect 8] The method according to any one of embodiments 3 to 7, wherein the recycled pulp fibers having the above-mentioned specified characteristics have a degree of polymerization of 300 or more.
[0023] The above method can form recycled pulp fibers having a specific range of polymerization degrees. Therefore, the above method can produce recycled pulp fibers suitable for applications where a decrease in polymerization degree is undesirable, such as rayon raw materials, cellophane raw materials, and cellulose nanofiber raw materials.
[0024] [Aspect 9] The method according to any one of embodiments 3 to 8, wherein the recycled pulp fibers having the above-mentioned predetermined characteristics have a reduction in the degree of polymerization of 400 or less, based on the above-mentioned pulp fibers.
[0025] The above method makes it possible to form recycled pulp fibers having a specific range of polymerization degrees based on pulp fibers. Therefore, the above method can produce recycled pulp fibers suitable for applications where a decrease in the degree of polymerization is undesirable.
[0026] [Aspect 10] The method according to any one of embodiments 3 to 9, wherein the recycled pulp fibers having the above-mentioned specified properties have an alkali solubility of 0 to 20% by mass.
[0027] The above method can form recycled pulp fibers having an alkali solubility within a specific range. Therefore, the above method can produce recycled pulp fibers suitable for applications where a decrease in alkali solubility is undesirable, such as for use as a raw material for rayon or cellophane.
[0028] [Aspect 11] The method according to any one of embodiments 1 to 10, wherein the recycled pulp fibers have an increase in alkali solubility of 0 to 16% by mass, based on the pulp fibers.
[0029] The above method allows for the formation of recycled pulp fibers having a specific range of alkali solubility, based on pulp fibers. Therefore, the above method can produce recycled pulp fibers suitable for applications where a decrease in alkali solubility is undesirable.
[0030] [Aspect 12] The method according to any one of embodiments 1 to 11, wherein in the recycled pulp fiber formation step described above, the oxidizing agent and the ultraviolet light are supplied to the aqueous solution in an overlapping manner.
[0031] In the above method, since ultraviolet light and an oxidizing agent are supplied in a redundant manner, the time required for the recycled pulp fiber formation step can be shortened, thus enabling the above method to be implemented efficiently.
[0032] [Aspect 13] The method according to any one of embodiments 1 to 12, wherein in the recycled pulp fiber formation step, the supply of the oxidizing agent to the aqueous solution is started, and then the supply of ultraviolet light to the aqueous solution is started.
[0033] For example, if the sanitary product is a used sanitary product, the aqueous solution containing a mixture of pulp fibers and superabsorbent polymers tends to become cloudy due to the excrement contained in the used sanitary product. Ultraviolet light tends to penetrate turbid aqueous solutions poorly and is less likely to oxidize and decompose superabsorbent polymers in turbid aqueous solutions. In the above method, since ultraviolet light is supplied to the aqueous solution after the oxidizing agent has been introduced, the ultraviolet light can efficiently oxidize and decompose the superabsorbent polymer.
[0034] [Aspect 14] The method according to any one of embodiments 1 to 13, wherein in the recycled pulp fiber formation step, the supply of the oxidizing agent to the aqueous solution is stopped, and then the supply of the ultraviolet light to the aqueous solution is stopped.
[0035] In the above method, since the supply of ultraviolet light is stopped after the supply of the oxidizing agent is stopped, the superabsorbent polymer can be efficiently oxidized and decomposed by the oxidizing agent remaining in the aqueous solution after the supply of the oxidizing agent has stopped. Furthermore, since the recycled pulp fiber recovery step can be carried out after the amount of oxidizing agent remaining in the aqueous solution has decreased, it is highly safe.
[0036] [Aspect 15] The method according to any one of embodiments 1 to 14, wherein in the recycled pulp fiber formation step, the supply of ultraviolet light to the aqueous solution is started, and then the supply of the oxidizing agent to the aqueous solution is started.
[0037] In the above method, since the oxidizing agent is supplied to the aqueous solution after the supply of ultraviolet light is started, the superabsorbent polymer can be oxidized and decomposed without, for example, performing a step to dehydrate the superabsorbent polymer before the recycled pulp fiber formation step.
[0038] [Aspect 16] The method according to any one of embodiments 1 to 15, wherein the ultraviolet light described above includes ultraviolet light with a wavelength of 380 nm or less. In the above method, since ultraviolet light includes wavelengths with specific wavelengths, the effect of Embodiment 1 is high.
[0039] [Aspect 17] A method for producing recycled pulp fibers having predetermined properties according to their intended use, from a mixture containing pulp fibers obtained from sanitary products and a superabsorbent polymer, A recycled pulp fiber forming step involves supplying an oxidizing agent and ultraviolet light to an aqueous solution containing the above mixture to oxidize and decompose the superabsorbent polymer, dissolving the oxidized superabsorbent polymer in the aqueous solution, and forming recycled pulp fibers having the predetermined properties. A recycled pulp fiber recovery step in which the above recycled pulp fibers are recovered, The above method, characterized by including the following.
[0040] The inventors of this application have found that while oxidizing agents are less affected by the transparency of aqueous solutions and can oxidatively decompose and remove superabsorbent polymers, in cases where the superabsorbent polymers are dehydrated, it is necessary to expose the pulp fibers to the oxidizing agent for a long time in order to oxidatively decompose the superabsorbent polymers. As a result, the degree of polymerization, carboxyl group content, alkali solubility, etc. of the recycled pulp fibers formed tend to change. This fact may be desirable depending on the application of the recycled pulp fibers, but may be undesirable depending on the application.
[0041] Furthermore, the inventors of this application have found that ultraviolet light can oxidize and decompose superabsorbent polymers, although it is affected by the transparency of the aqueous solution, and remove them, while not significantly altering the properties of the recycled pulp fibers formed.
[0042] In the above method, in the recycled pulp fiber formation step, a mixture containing pulp fibers and a superabsorbent polymer is supplied to an aqueous solution with an adjusted ratio of oxidizing agent and ultraviolet light to form recycled pulp fibers having predetermined properties according to the application. Therefore, the formed recycled pulp fibers are less likely to contain superabsorbent polymer and its residue, and have appropriate predetermined properties according to the application, making them useful for that application.
[0043] The method for producing recycled pulp fibers from a mixture containing pulp fibers obtained from sanitary products and a superabsorbent polymer (hereinafter sometimes simply referred to as the "method for producing recycled pulp fibers") described in this disclosure will be explained in detail below.
[0044] [Method for manufacturing recycled pulp fibers] The method for producing recycled pulp fibers from a mixture containing pulp fibers obtained from sanitary products and a superabsorbent polymer, as disclosed herein, includes the following steps: - A recycled pulp fiber formation step (hereinafter sometimes referred to as the "recycled pulp fiber formation step") is performed by supplying ultraviolet light and an oxidizing agent to an aqueous solution containing the above mixture, thereby oxidatively decomposing the superabsorbent polymer, dissolving the oxidatively decomposed superabsorbent polymer in the aqueous solution, and forming the recycled pulp fibers. • A recycled pulp fiber recovery step (hereinafter sometimes referred to as the "recycled pulp fiber recovery step") for recovering the recycled pulp fibers mentioned above.
[0045] The method for producing recycled pulp fibers relating to this disclosure may further include the following steps as optional steps: • A dehydration step (hereinafter sometimes simply referred to as the "dehydration step") is performed before the above-mentioned recycled pulp fiber formation step to dehydrate the above-mentioned superabsorbent polymer.
[0046] <Recycled pulp fiber formation step> The above-mentioned sanitary products are not particularly limited as long as they contain pulp fibers and superabsorbent polymers, and examples include disposable diapers, incontinence pads, sanitary napkins, bed sheets, pet sheets, etc. The above-mentioned sanitary products include sanitary products used by a user that have absorbed the user's excrement, sanitary products used by a user that have not absorbed the user's excrement, unused sanitary products that have been discarded, and defective products from the manufacturing of sanitary products.
[0047] The pulp fibers mentioned above are not particularly limited as long as they are used in sanitary products, and examples include wood pulp (e.g., softwood pulp, hardwood pulp), non-wood pulp, and cross-linked pulp.
[0048] Examples of the superabsorbent polymers mentioned above include those used in hygiene products, such as starch-based, cellulose-based, and synthetic polymer-based superabsorbent polymers. Examples of starch-based or cellulose-based superabsorbent polymers include starch-acrylic acid (salt) graft copolymers, saponified starch-acrylonitrile copolymers, and crosslinked sodium carboxymethylcellulose. Examples of synthetic polymer-based superabsorbent polymers include polyacrylate-based, polysulfonate-based, maleate-anhydride-based, polyacrylamide-based, polyvinyl alcohol-based, polyethylene oxide-based, polyaspartate-based, polyglutamate-based, polyalginate-based, starch-based, and cellulose-based superabsorbent polymers (SAP, Super Absorbent Polymer).
[0049] The method for obtaining an aqueous solution containing a mixture of pulp fibers and a superabsorbent polymer from the above-mentioned sanitary products is not particularly limited. For example, it can be obtained by cutting up used sanitary products, obtaining a mixture containing pulp fibers and a superabsorbent polymer from the absorbent material, and dispersing the mixture in water. Alternatively, for example, used sanitary products can be cut up in water to obtain an aqueous solution containing a mixture of pulp fibers and a superabsorbent polymer from the absorbent material.
[0050] In the above aqueous solution, the superabsorbent polymer may or may not be dehydrated using a dehydrating agent. If the superabsorbent polymer is not dehydrated, the dehydration step for the superabsorbent polymer can be omitted, and the resulting recycled pulp fibers are less likely to contain the superabsorbent polymer and its residue, as well as the dehydrating agent and its residue. If the superabsorbent polymer is dehydrated, the above aqueous solution can be reduced to a predetermined moisture content, and the superabsorbent polymer can be efficiently oxidatively decomposed and removed while maintaining a high concentration in the aqueous solution.
[0051] When the superabsorbent polymer has been dehydrated with a dehydrating agent, it is preferable that the superabsorbent polymer has been dehydrated to have a water absorption ratio of preferably 50 times or less, more preferably 30 times or less, even more preferably 25 times or less, and even more preferably 20 times or less. Furthermore, when the superabsorbent polymer has been dehydrated, it is preferable that the superabsorbent polymer has been dehydrated to have a water absorption ratio of preferably 1 time or more, more preferably 2 times or more, even more preferably 3 times or more, and even more preferably 4 times or more. This allows for efficient oxidative decomposition and removal of the superabsorbent polymer while maintaining a high concentration in the aqueous solution. The dehydrating agent will be explained in the section on the desired dehydration step.
[0052] When the superabsorbent polymer has been dehydrated with a dehydrating agent, the aqueous solution preferably has a solid content concentration of 4.0% by mass or less, more preferably 3.5% by mass or less, and even more preferably 3.0% by mass or less. Furthermore, the aqueous solution preferably has a solid content concentration of 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1.0% by mass or more. This allows for efficient oxidative decomposition and removal of the superabsorbent polymer while maintaining a high concentration in the aqueous solution. The above solid content concentration is particularly preferable when the aqueous solution is continuously stirred.
[0053] If the superabsorbent polymer has not been dehydrated by a dehydrating agent, the aqueous solution preferably has a solid content concentration of 0.1% by mass or less, more preferably 0.075% by mass or less, and even more preferably 0.05% by mass or less. Alternatively, the aqueous solution may have a solid content concentration of 0.01% by mass or more, more preferably 0.02% by mass or more, and even more preferably 0.03% by mass or more. This allows for efficient oxidative decomposition and removal of the superabsorbent polymer. The above solid content concentration is particularly preferable when the aqueous solution is continuously stirred.
[0054] In this specification, the solid content concentration is calculated by subtracting the moisture content from 100. The moisture content is measured using Kett's FD-720 infrared moisture meter. Specifically, approximately 5g of the sample is placed in the FD-720's sample dish, the temperature is set to 150°C, and the automatic stop mode is selected to measure the moisture content of the sample.
[0055] The oxidizing agent used in the recycled pulp fiber formation step is not particularly limited as long as it can oxidize and decompose the superabsorbent polymer. Examples include ozone, hydrogen peroxide, chlorine dioxide, peracetic acid, sodium hypochlorite, etc., with ozone being preferred.
[0056] The ozone is preferably supplied to the aqueous solution as an ozone-containing gas (for example, by being blown in), and the ozone-containing gas is preferably supplied to the aqueous solution as small bubbles (for example, microbubbles or nanobubbles) (for example, by being blown in).
[0057] The ozone-containing gas is supplied to the aqueous solution such that the CT value, which is the product of the ozone concentration in the ozone-containing gas and the treatment time, exceeds 600 ppm·min, preferably 800 ppm·min or more, more preferably 900 ppm·min or more, even more preferably 1,000 ppm·min or more, and even more preferably 1,200 ppm·min or more. The ozone-containing gas is supplied to the aqueous solution such that the CT value, which is the product of the ozone concentration in the ozone-containing gas and the treatment time, is preferably 12,000 ppm·min or less, more preferably 8,000 ppm·min or less, and even more preferably 6,000 ppm·min or less. This makes it easier to oxidize and decompose the superabsorbent polymer while keeping the properties of the recycled pulp fibers within the desired range.
[0058] The ozone concentration in the above ozone-containing gas is preferably 30 to 200 ppm (g / m³). 3 ), more preferably 80-200 ppm (g / m³) 3 ), and more preferably 100-200 ppm (g / m³). 3 This makes it easier to maintain the properties of recycled pulp fibers within the desired range while oxidatively decomposing the superabsorbent polymer. The ozone concentration in ozone-containing gases can be measured, for example, using an ultraviolet absorption type ozone meter (e.g., Eco Design Co., Ltd.'s Ozone Monitor OZM-5000G).
[0059] The ozone concentration in the above aqueous solution is preferably 1 to 50 ppm (g / m³). 3 ), more preferably 2-40 ppm (g / m³) 3 ), and more preferably 3-30 ppm (g / m³) 3 )
[0060] The ozone concentration in an aqueous solution is measured by the following method. (1) Add 85 mL of an aqueous solution containing dissolved ozone to a 100 mL graduated cylinder containing approximately 0.15 g of potassium iodide and 5 mL of a 10% by mass citric acid solution, and allow the reaction to proceed. (2) Transfer the aqueous solution after the reaction to a 200 mL Erlenmeyer flask, add starch solution to the Erlenmeyer flask, and after it turns purple, titrate with 0.01 mol / L sodium thiosulfate while stirring until it becomes colorless, and record the amount added: a (mL). (3) The ozone concentration in the aqueous solution is calculated using the following formula. The ozone concentration (mass ppm) in an aqueous solution is expressed by the following formula: Ozone concentration (mass ppm) in aqueous solution = a(mL) × 0.24 × 0.85(mL)
[0061] The ultraviolet light used in the recycled pulp fiber formation step preferably includes ultraviolet light with a wavelength of 380 nm or less, more preferably 290 nm or less, even more preferably 260 nm or less, and even more preferably 200 nm or less. Furthermore, the ultraviolet light preferably includes ultraviolet light with a wavelength of 100 nm or more, more preferably 150 nm or more, and even more preferably 160 nm or more. This allows for the oxidative decomposition of the superabsorbent polymer with highly energy-efficient ultraviolet light while suppressing changes in the properties of the recycled pulp fibers.
[0062] Examples of ultraviolet light sources include low-pressure mercury lamps, high-pressure mercury lamps, and deep ultraviolet LEDs. An example of a product name for an ultraviolet light source is the PAQ-15ESET (processing capacity 8 liters / minute) deep ultraviolet light generator / UV-LED irradiated water sterilization module manufactured by Nikkiso Giken Co., Ltd. The ultraviolet light described above can be irradiated onto the aqueous solution by, for example, placing the device that emits the ultraviolet light inside the aqueous solution or by placing it at a distance from the aqueous solution.
[0063] There are no particular restrictions on the uses of the recycled pulp fibers mentioned above. Examples include pulp fiber applications where the fibers are used as is (for example, the aforementioned hygiene products) and processing applications (for example, cellulose raw material applications). Examples of the above-mentioned applications for cellulose raw materials include cellulose nanofibers, viscose rayon, cellulose derivatives, bioethanol, biobutanol, molding materials, and paper products.
[0064] The oxidizing agent and ultraviolet light described above can be supplied to the aqueous solution according to the intended use of the recycled pulp fibers. The oxidizing agents mentioned above tend to lower the degree of polymerization of recycled pulp fibers, increase the amount of carboxyl groups, and increase the alkali solubility. On the other hand, ultraviolet light tends to result in smaller differences in properties between pulp fibers before and after the recycled pulp fiber formation step, such as changes in the degree of polymerization, the amount of carboxyl groups, and the alkali solubility.
[0065] Therefore, when oxidatively decomposing superabsorbent polymers, appropriate recycled pulp fibers can be formed depending on the application by changing the ratio of the oxidizing agent to ultraviolet light. Applications where the relative proportion of oxidizing agents should be increased include, for example, processing applications (e.g., cellulose raw material applications). Applications where the relative proportion of ultraviolet light should be increased include, for example, pulp fiber applications where recycled pulp fibers are used as pulp fibers (e.g., the aforementioned hygiene products).
[0066] In the recycled pulp fiber formation step described above, the oxidizing agent and ultraviolet light can be supplied to the aqueous solution in an overlapping manner (hereinafter sometimes referred to as "overlapping supply"), and the oxidizing agent and ultraviolet light can be supplied to the aqueous solution without overlapping (hereinafter sometimes referred to as "non-overlapping supply"). The aforementioned duplicate supply allows for a reduction in the time required for the recycled pulp fiber formation step, thus enabling the above method to be implemented efficiently. By using the above-mentioned non-duplicate supply method, for example, the recycled pulp fiber formation step can be carried out while checking the condition of the pulp fibers (recycled pulp fibers) or while confirming the characteristics of the recycled pulp fibers.
[0067] In the above-mentioned duplicate and non-duplicate supply scenarios, the supply of the oxidizing agent can be initiated, followed by the supply of ultraviolet light. This allows the ultraviolet light to efficiently oxidize and decompose the superabsorbent polymer, especially when the sanitary product is a used product. Furthermore, in the above-mentioned overlapping and non-overlapping supply processes, the supply of ultraviolet light can be initiated, followed by the supply of the oxidizing agent. This allows, for example, the superabsorbent polymer to be oxidized and decomposed without performing a step to dehydrate the superabsorbent polymer before the recycled pulp fiber formation step.
[0068] In the above-mentioned duplicate and non-duplicate supply processes, the supply of the oxidizing agent can be stopped, followed by the stop of the ultraviolet light supply. This allows the superabsorbent polymer to be efficiently oxidized and decomposed by the oxidizing agent remaining in the aqueous solution. Furthermore, since the recycled pulp fiber recovery step can be carried out after the amount of oxidizing agent remaining in the aqueous solution has decreased, safety is ensured. Furthermore, in the above-mentioned overlapping and non-overlapping supply processes, the supply of ultraviolet light can be stopped, followed by the supply of the oxidizing agent. This allows, for example, the condition of the pulp fibers (recycled pulp fibers) to be visually checked after the supply of ultraviolet light has been stopped, and then the supply of the oxidizing agent can be stopped.
[0069] In the recycled pulp fiber formation step, recycled pulp fibers can be formed to have a carboxyl group content appropriate to their intended use. The recycled pulp fibers preferably have a carboxyl group content in the range of 0 to 0.075 mmol / g, more preferably 0.010 to 0.070 mmol / g, even more preferably 0.010 to 0.065 mmol / g, and even more preferably 0.010 to 0.060 mmol / g. This makes it possible to produce recycled pulp fibers suitable for applications where the formation of carboxyl groups is undesirable, such as raw materials for cellulose derivatives like acetate, rayon, and cellophane.
[0070] The recycled pulp fibers described above have an increase in carboxyl groups of preferably 0 to 0.035 mmol / g, more preferably 0.010 to 0.030 mmol / g, even more preferably 0.010 to 0.025 mmol / g, and even more preferably 0.010 to 0.020 mmol / g, relative to the pulp fibers before the recycled pulp fiber formation step. This makes it possible to produce recycled pulp fibers suitable for applications where the formation of carboxyl groups is undesirable.
[0071] In this specification, the carboxyl group content: C (mmol / g) of pulp fibers and recycled pulp fibers (hereinafter sometimes simply referred to as "pulp fibers") is measured as follows. (1) Add approximately 0.4 g of pulp fiber to a container to which 170 mL of deionized water has been added, and disperse the pulp fiber in the deionized water. (2) Add 10 mL of 0.01 M NaCl to the container. (3) Add 0.1M HCl to the container and adjust the pH to 2.8.
[0072] (4) Add 0.05 M NaOH to the container at a rate of 0.1 mL / min to 0.2 mL / min until the pH reaches 11, and monitor the electrical conductivity of the contents of the container. (5) Plot the amount of 0.05M NaOH added on the X-axis and the electrical conductivity on the Y-axis, and determine the amount of 0.05M NaOH added (V(mL)) at which the electrical conductivity becomes constant. (6) The pulp fibers are recovered by filtration, and their oven-dry mass: m1 (g) is measured.
[0073] (7) The amount of carboxyl groups in pulp fibers: C (mmol / g) is given by the following formula: C(mmol / g) = (V × 0.05 / 1000) / m1 It is calculated by [method]. pH will be measured using a pHashion pH meter, model C-62, manufactured by AS ONE Corporation. Electrical conductivity will be measured using a portable electrical conductivity meter (CM-31P type), manufactured by Toa DKK Corporation.
[0074] In the recycled pulp fiber formation step, recycled pulp fibers can be formed to have a degree of polymerization appropriate for their intended use. The recycled pulp fibers preferably have a degree of polymerization of 300 or more, more preferably 350 or more, even more preferably 400 or more, even more preferably 450 or more, and even more preferably 500 or more. This makes it possible to produce recycled pulp fibers suitable for applications where a decrease in the degree of polymerization is undesirable, such as raw materials for rayon, cellophane, and cellulose nanofibers.
[0075] The recycled pulp fibers described above have a degree of polymerization reduction of preferably 400 or less, more preferably 300 or less, even more preferably 200 or less, and even more preferably 150 or less, relative to the pulp fibers before the recycled pulp fiber formation step. This makes it possible to produce recycled pulp fibers suitable for applications where a reduction in the degree of polymerization is undesirable.
[0076] In this specification, the degree of polymerization (DP) of pulp fibers and recycled pulp fibers (hereinafter sometimes simply referred to as "pulp fibers") is measured as follows. (1) According to "6.4.1 Viscosity Ratio" of "Cellulose Dilute Solution - Method for Measuring Limiting Viscosity Number - Cuprammonium Ethylenediamine Method" specified in JIS 8215:1998, measure the viscosity ratio η r (= η / η0) of the pulp fibers.
[0077] (2) Using the following formula, calculate the degree of polymerization (DP) of the pulp fibers. Specific viscosity: η sp = η r - 1 Intrinsic viscosity: [η] = η sp / (100 × c(1 + 0.28η sp )) Degree of polymerization: DP = 175 × [η] Note that the above formula is based on the description on page 101 of the Wood Science Experiment Manual (edited by the Japan Wood Research Society, published by Bun'eido, 2000), and c means the cellulose concentration (g / mL).
[0078] In the recycled pulp fiber forming step, the recycled pulp fibers can be formed to have an alkali dissolution rate according to their intended use. The above recycled pulp fibers preferably have an alkali dissolution rate of 0 to 20% by mass, more preferably 1 to 17% by mass, still more preferably 1 to 14% by mass, and even more preferably 1 to 12% by mass. Thereby, recycled pulp fibers suitable for applications where a decrease in the alkali dissolution rate is not preferable, such as for rayon raw materials, cellophane raw materials, etc., can be produced.
[0079] The above recycled pulp fibers preferably have an increase in alkali solubility of 0 to 16% by mass, more preferably 1 to 13% by mass, still more preferably 1 to 10% by mass, and even more preferably 1 to 7% by mass, based on the pulp fibers before the recycled pulp fiber forming step. Thereby, recycled pulp fibers suitable for applications where a decrease in the alkali solubility is not preferable can be produced.
[0080] In this specification, the alkali solubility of pulp fibers and recycled pulp fibers (hereinafter sometimes simply referred to as "pulp fibers") is measured as follows. (1) Immerse a pulp fiber (approximately 1.0 g) with a mass of m² (g) in 50 mL of 5 M sodium hydroxide solution and let it stand for 1 hour. (2) The sodium hydroxide aqueous solution is subjected to a centrifuge to separate the supernatant from the precipitate, and the precipitate is obtained by filtration, neutralized, and then dried at 70°C. (3) Allow the precipitate to dry completely and measure its dry mass: m3 (g). (4) Alkali solubility: S (mass%) is given by the following formula: S (mass%)=100×(m2-m3) / m2 It is calculated by [method].
[0081] <Recycled pulp fiber recovery step> In the recycled pulp fiber recovery step, recycled pulp fibers are recovered. In the recycled pulp fiber recovery step, for example, recycled pulp fibers can be recovered from the aqueous solution using, for example, a screen having multiple openings.
[0082] <Dehydration Step> The manufacturing method according to this disclosure may further include, as an optional step, a dehydration step of dehydrating the superabsorbent polymer before the recycled pulp fiber formation step. This reduces the amount of waste contained in the superabsorbent polymer and lowers the viscosity of the superabsorbent polymer, and consequently the viscosity of the aqueous solution containing the pulp fibers and the superabsorbent polymer, allowing the recycled pulp fiber formation step to be carried out in an aqueous solution with a low water content (high solid content).
[0083] The dehydration step can be carried out, for example, by adding a dehydrating agent to an aqueous solution containing a mixture of pulp fibers and a superabsorbent polymer, or by immersing the pulp fibers and superabsorbent polymer (or the sanitary product itself) in an aqueous solution containing a dehydrating agent.
[0084] Examples of the above-mentioned dehydrating agents include acids (e.g., inorganic acids and organic acids), lime, calcium chloride, magnesium sulfate, magnesium chloride, aluminum sulfate, and aluminum chloride. Acids are preferred because they do not easily leave ash residue on recycled pulp fibers. When an acid is used as the dehydrating agent, the aqueous solution preferably has a pH of 2.5 or less, and more preferably 1.3 to 2.4. This sufficiently reduces the water absorption capacity of the superabsorbent polymer, reduces the risk of equipment corrosion, and reduces the need for large amounts of alkaline chemicals in the neutralization treatment during wastewater treatment.
[0085] Examples of the inorganic acids mentioned above include sulfuric acid, hydrochloric acid, and nitric acid, but sulfuric acid is preferred from the viewpoint of not containing chlorine and cost. Examples of the organic acids mentioned above include citric acid, tartaric acid, glycolic acid, malic acid, succinic acid, acetic acid, and ascorbic acid, but acids that can form complexes with metal ions contained in excrement, such as hydroxycarbonate organic acids like citric acid, tartaric acid, and gluconic acid, are particularly preferred. Calcium ions are an example of metal ions contained in excrement. This is because the chelating effect of acids that can form complexes with metal ions contained in excrement traps and removes metal ions in the excrement. Furthermore, citric acid can be expected to have a high dirt removal effect due to its cleaning effect.
[0086] In the dehydration step, the superabsorbent polymer is dehydrated so that it has a water absorption ratio of preferably 50 times or less, more preferably 30 times or less, even more preferably 25 times or less, and even more preferably 20 times or less, and preferably 1 time or more, more preferably 2 times or more, even more preferably 3 times or more, and even more preferably 4 times or more. By doing so, the viscosity of the aqueous solution can be maintained within a predetermined range, and the superabsorbent polymer can be efficiently oxidized and decomposed.
[0087] The above water absorption ratio is measured as follows: (1) Place the superabsorbent polymer in a mesh and suspend it for 5 minutes to remove any moisture adhering to its surface, then measure its pre-drying mass: m4(g). (2) The superabsorbent polymer is dried at 120°C for 10 minutes, and its mass after drying: m5 (g) is measured. (3) The water absorption ratio (g / g) is given by the following formula: Water absorption capacity (g / g)=100×m4 / m5 It is calculated by [method].
[0088] Furthermore, the optional dewatering step can be carried out simultaneously with the recycled pulp fiber formation step. This allows the method according to this disclosure to be carried out efficiently. [Examples]
[0089] The following examples illustrate this disclosure, but this disclosure is not limited to these examples. [Reference example 1] A mixture of 1.0 g of pulp fiber (coniferous pulp fiber) and 0.5 g of superabsorbent polymer (Sumitomo Seika Co., Ltd., AquaKeep®, SA60S) was placed in a mesh bag (25 cm square, NBC Mesh Tech Co., Ltd., N-No.250HD). The mixture, along with the mesh bag, was immersed in 80 mL of physiological saline for 15 minutes to allow the superabsorbent polymer (SAP) to absorb the saline solution. Next, the mixture was immersed in a pH 2.0 aqueous sulfuric acid solution containing sulfuric acid as a dehydrating agent for 15 minutes to dehydrate the superabsorbent polymer and form mixture No. 1. The pulp fibers and superabsorbent polymer placed in the mesh bag were dried at 120°C for 10 minutes.
[0090] Mixture No. 1 in the mesh bag is placed under a low-pressure mercury lamp (manufactured by Sen Special Light Source Co., Ltd., UVL20PH-6, discharge tube power: 0.05W / cm²). 2 The mixture was placed in a photochemical reactor (GT500, container capacity: 500 mL) manufactured by Global Top Chemical Co., Ltd., and deionized water was used to form a dispersed aqueous solution No. 1 (600 mL) of a mixture of pulp fibers and superabsorbent polymer with a solid content concentration of 0.25% by mass. Dispersed aqueous solution No. 1 was continuously stirred with a stirrer. Note that the container capacity of the GT500 refers to the minimum volume of contents.
[0091] Ultraviolet light was irradiated onto dispersed aqueous solution No. 1 from a low-pressure mercury lamp for 30 minutes to oxidize and decompose the superabsorbent polymer. Next, the contents of the photochemical reactor were filtered, and the filter was washed with deionized water.
[0092] The filtrate, washed with deionized water, was dried at 120°C for 10 minutes, and the dry mass of the dried filtrate (m6 g) was measured. The percentage of remaining filtrate, R (mass %), is given by the following formula: R (mass%)=100×m6 / 1.5 It was calculated using the method described below. The results are shown in Table 1.
[0093] [Reference example 2] The superabsorbent polymer was oxidatively decomposed in the same manner as in Reference Example 1, except that it was not dehydrated using a dehydrating agent. The remaining percentage of the filtered material is shown in Table 1.
[0094] [Reference example 3] The remaining percentage of the filtered material was measured in the same manner as in Reference Example 1, except that only 1.0 g of pulp fiber (without 0.5 g of superabsorbent polymer) was placed in a mesh bag. The results are shown in Table 1. [Reference example 4] The remaining percentage of the filtered material was measured in the same manner as in Reference Example 1, except that only 0.5g of superabsorbent polymer (without 1.0g of pulp fiber) was placed in a mesh bag. The results are shown in Table 1.
[0095] [Reference example 5] Mixture No. 1 was formed in the same manner as in Reference Example 1. Mixture No. 1 in a mesh container and deionized water were added to a 2L ozone gas exposure tank to form aqueous dispersion No. 1 (600mL) of pulp fibers and superabsorbent polymer with a solid content concentration of 0.25% by mass. The ozone concentration was 50g / m³ from an ozone generator (Ecodesign Co., Ltd., ozone gas exposure tester: ED-OWX-2). 3 Furthermore, an ozone-containing gas (with dry air as the only gas) adjusted to a flow rate of 1 L / min was blown into the dispersed aqueous solution No. 1 in the ozone gas exposure tank for 30 minutes to oxidize and decompose the superabsorbent polymer. The remaining percentage of the filtered material is shown in Table 1.
[0096] [Reference example 6] The superabsorbent polymer was oxidatively decomposed in the same manner as in Reference Example 5, except that the superabsorbent polymer was not dehydrated using a dehydrating agent. The remaining percentage of the filtrate is shown in Table 1.
[0097] [Reference example 7] The remaining percentage of the filtered material was measured in the same manner as in Reference Example 5, except that only 1.0 g of pulp fiber (without 0.5 g of superabsorbent polymer) was placed in a mesh bag. The results are shown in Table 1. [Reference example 8] The remaining percentage of the filtered material was measured in the same manner as in Reference Example 5, except that only 0.5g of superabsorbent polymer (without 1.0g of pulp fiber) was placed in the mesh bag. The results are shown in Table 1.
[0098] [Table 1]
[0099] From Reference Examples 1 to 4, it can be seen that when UV light was used, all of the superabsorbent polymer was oxidatively decomposed, while all of the pulp fibers remained intact. On the other hand, from Reference Examples 7 and 8, it can be seen that when ozone is used, not all of the superabsorbent polymer is oxidatively decomposed, and some of the superabsorbent polymer remains, resulting in a higher retention rate of the filtered material in Reference Examples 5 and 6.
[0100] [Reference example 9] Pulp fibers (coniferous pulp fibers) were dispersed in deionized water to form a 0.25% by mass pulp fiber dispersion aqueous solution No. 2 (600 mL). Dispersion aqueous solution No. 2 was heated under a low-pressure mercury lamp (manufactured by Sen Special Light Source Co., Ltd., UVL20PH-6, discharge tube power: 0.05 W / cm²). 2 The solution was placed in a photochemical reactor (GT500, container capacity: 500 mL) manufactured by Global Top Chemical Co., Ltd., and the dispersed aqueous solution No. 2 was continuously stirred with a stirrer. Ultraviolet light was irradiated onto dispersed aqueous solution No. 2 from a low-pressure mercury lamp for a predetermined time, and the amount of carboxyl groups, degree of polymerization, and alkali solubility at that time were measured. The results are shown in Tables 2, 3, and 4.
[0101] [Reference example 10] Replace the low-pressure mercury lamp with a high-pressure mercury lamp (Sen Special Light Source Co., Ltd., HL100GL-1, discharge tube power: 8W / cm²). 2 Except for the change made to ), the amount of carboxyl groups, degree of polymerization, and alkali solubility at a predetermined time were measured in the same manner as in Reference Example 9. The results are shown in Tables 2, 3, and 4.
[0102] [Reference example 11] Pulp fibers (coniferous pulp fibers) and deionized water were added to a 2L ozone gas exposure tank to form pulp fiber dispersion aqueous solution No. 3 (600mL) with a solid content concentration of 0.25% by mass. The ozone concentration was 50g / m³ from an ozone generator (Ecodesign Co., Ltd., ozone gas exposure test machine: ED-OWX-2). 3 Furthermore, an ozone-containing gas (with dry air as the only gas other than ozone) adjusted to a flow rate of 1 L / min was blown into dispersed aqueous solution No. 3 in an ozone gas exposure tank for 30 minutes. The ozone concentration in dispersed aqueous solution No. 3 was approximately 6 ppm. The amount of carboxyl groups, degree of polymerization, and alkali solubility were tracked at a predetermined time. The results are shown in Tables 2, 3, and 4.
[0103] [Table 2]
[0104] [Table 3]
[0105] [Table 4]
[0106] Table 2 shows that when pulp fibers are irradiated with ultraviolet light from low-pressure and high-pressure mercury lamps, the amount of carboxyl groups in the pulp fibers does not increase as much as when they are exposed to ozone, meaning that the pulp fibers are less likely to be oxidized. Furthermore, Table 3 shows that when pulp fibers are irradiated with ultraviolet light from low-pressure and high-pressure mercury lamps, the degree of polymerization of the pulp is less likely to decrease compared to when the pulp fibers are exposed to ozone.
[0107] Furthermore, Table 4 shows that when pulp fibers are irradiated with ultraviolet light from low-pressure and high-pressure mercury lamps, the alkali solubility does not increase as much compared to when pulp fibers are exposed to ozone. Note that the pulp fibers in Reference Example 11 showed discoloration in the oven-dried precipitate.
[0108] Combining Tables 2-4 with Table 1, it can be seen that UV light is excellent at oxidative decomposition of superabsorbent polymers and is less likely to alter pulp fibers. Ozone, although inferior to UV light, is also excellent at oxidative decomposition of superabsorbent polymers and is somewhat likely to alter pulp.
[0109] Based on the above, when recycled pulp fibers are used for pulp fiber applications, increasing the ratio of UV light to an oxidizing agent (e.g., ozone) can form recycled pulp fibers with properties similar to those of the original pulp fibers. When recycled pulp fibers are used for processing applications, increasing the ratio of an oxidizing agent to an oxidizing agent (e.g., ozone) can form recycled pulp fibers with desired properties.
[0110] [Example 1] A mixture of 3.0 g of pulp fiber (coniferous pulp fiber) and 1.5 g of superabsorbent polymer (Sumitomo Seika Co., Ltd., AquaKeep®, SA60S) was placed in a mesh bag (25 cm square, NBC Mesh Tech Co., Ltd., N-No.250HD). The mixture, along with the mesh bag, was immersed in 80 mL of physiological saline for 15 minutes to allow the superabsorbent polymer (SAP) to absorb the saline solution. Next, the mixture was immersed in 700 mL of a pH 2.0 aqueous sulfuric acid solution containing sulfuric acid as a dehydrating agent for 15 minutes to dehydrate the superabsorbent polymer and form mixture No. 2. The pulp fibers and superabsorbent polymer placed in the mesh bag were dried at 120°C for 10 minutes.
[0111] Mixture No. 2 in the mesh, deionized water, and 10 mL of milk were mixed to form aqueous dispersion No. 4 (600 mL) of pulp fibers and superabsorbent polymer with a solid content concentration of 0.75% by mass. The 10 mL of milk was added to make the aqueous dispersion cloudy, simulating a situation where the aqueous dispersion is cloudy due to the presence of excrement, etc.
[0112] The transparency of dispersed aqueous solution No. 4 was 1.0. The above transparency values were measured using the AT-1 acrylic transparency meter from the AT series, manufactured by Kasahara Chemical Industries.
[0113] [Ozone treatment] A dispersion aqueous solution No. 4 (600 mL) of pulp fibers and superabsorbent polymer was heated under a low-pressure mercury lamp (manufactured by Sen Special Light Source Co., Ltd., UVL20PH-6, discharge tube power: 0.05 W / cm²). 2 The solution was placed in a photochemical reactor (GT500, container capacity: 500 mL) manufactured by Global Top Chemical Co., Ltd., and the dispersed aqueous solution No. 4 was continuously stirred with a stirrer.
[0114] The above photochemical reaction apparatus is subjected to an ozone generator (manufactured by Eco Design Co., Ltd., ozone gas exposure tester: ED-OWX-2) with an ozone concentration of 50 g / m³. 3 Furthermore, an ozone-containing gas (with dry air as the only other gas) adjusted to a flow rate of 1 L / min was blown in for 15 minutes to oxidize and decompose the superabsorbent polymer. Furthermore, ultraviolet light is not emitted from the low-pressure mercury lamp during this ozone treatment process.
[0115] [UV treatment] Ultraviolet light was irradiated from a low-pressure mercury lamp onto dispersed aqueous solution No. 4 (600 mL) for 15 minutes to oxidize and decompose the superabsorbent polymer. Note that no ozone-containing gas was blown in from an ozone generator during this UV treatment. Next, the contents of the photochemical reactor were filtered, and the filtrate was washed with deionized water to obtain recycled pulp fibers. Table 5 shows the remaining percentage of the superabsorbent polymer and the transparency of the dispersed aqueous solution No. 4 after exposure to ultraviolet light (transparency after treatment). The remaining percentage of the superabsorbent polymer was calculated assuming that the mass of the recycled pulp fibers was 3.0 g (the same as the mass of the pulp fibers). In Table 5, superabsorbent polymers are abbreviated as "SAP," and pulp fibers are abbreviated as "pulp."
[0116] [Comparative Example 1] Recycled pulp fibers were obtained in the same manner as in Example 1, except that the ozone treatment time was set to 30 minutes and UV treatment was omitted. The residual rate of superabsorbent polymer and the transparency after treatment are shown in Table 5. [Comparative Example 2] Recycled pulp fibers were obtained in the same manner as in Example 1, except that 10 mL of milk was not added to the dispersed aqueous solution No. 4, the UV treatment time was set to 30 minutes, and ozone treatment was not performed. The residual rate of superabsorbent polymer and the transparency after treatment are shown in Table 5.
[0117] [Reference example 12] The same procedure as in Example 1 was followed, except that 3.0 g of pulp fiber was not added, and a dispersed aqueous solution of superabsorbent polymer (No. 5, 600 mL) with a solid content concentration of 0.25% by mass was formed. The remaining percentage of superabsorbent polymer and the transparency after treatment are shown in Table 5.
[0118] [Reference example 13] The treatment was the same as in Reference Example 12, except that ozone treatment and UV treatment were performed simultaneously for 30 minutes. The remaining percentage of the superabsorbent polymer and the transparency after treatment are shown in Table 5. [Reference example 14] The treatment was the same as in Reference Example 12, except that 10 mL of milk was not added to dispersion aqueous solution No. 4, and ozone treatment and UV treatment were performed simultaneously for 30 minutes. The remaining percentage of the superabsorbent polymer and the transparency after treatment are shown in Table 5.
[0119] [Reference example 15] The treatment was the same as in Reference Example 12, except that ozone treatment was performed for 30 minutes and UV treatment was not performed. The remaining percentage of the superabsorbent polymer and the transparency after treatment are shown in Table 5. [Reference example 16] The treatment was the same as in Reference Example 12, except that 10 mL of milk was not added to dispersion aqueous solution No. 4, and ozone treatment was performed for 30 minutes, while UV treatment was not performed. The remaining percentage of the superabsorbent polymer and the transparency after treatment are shown in Table 5.
[0120] [Reference example 17] The treatment was the same as in Reference Example 12, except that UV treatment was performed for 30 minutes and ozone treatment was not performed. The remaining percentage of the superabsorbent polymer and the transparency after treatment are shown in Table 5. [Reference example 18] The treatment was the same as in Reference Example 12, except that 10 mL of milk was not added to dispersion aqueous solution No. 4, and UV treatment was performed for 30 minutes without ozone treatment. The remaining percentage of the superabsorbent polymer and the transparency after treatment are shown in Table 5.
[0121] [Table 5]
[0122] From a comparison between Example 1 and Comparative Example 1, and between Reference Example 12 and Reference Example 15, it can be seen that when ozone treatment and UV treatment are used in combination, the SAP retention rate is comparable to that when ozone treatment is used alone. Furthermore, since it is clear from Reference Examples 9-11 that the properties of recycled pulp fibers change as the ozone treatment time increases, it can be seen that the properties of recycled pulp fibers can be adjusted by using ozone treatment and UV treatment in combination.
Claims
1. A method for producing recycled pulp fibers from a mixture containing pulp fibers obtained from hygiene products and a superabsorbent polymer, comprising: a recycled pulp fiber forming step of oxidizing and decomposing the superabsorbent polymer by supplying an oxidizing agent and ultraviolet light to an aqueous solution containing the mixture, and dissolving the oxidatively decomposed superabsorbent polymer in the aqueous solution to form the recycled pulp fiber; a recycled pulp fiber recovery step of recovering the recycled pulp fibers; The method, characterized in that it comprises:
2. The method of claim 1 , wherein the oxidizing agent is ozone.
3. The recycled pulp fibers have predetermined properties according to the intended use, In the recycled pulp fiber forming step, the ratio of ultraviolet light and an oxidizing agent is adjusted and supplied to the aqueous solution to form recycled pulp fibers having predetermined properties according to the intended use.
3. The method according to claim 1 or 2.
4. The method according to claim 3 , wherein the application is a cellulose feedstock application.
5. The method according to claim 4, wherein the cellulose raw material application is selected from the group consisting of cellulose nanofiber, viscose rayon, cellulose derivatives, bioethanol, biobutanol, molding materials, and paper processed products.
6. The method according to any one of claims 3 to 5, wherein the recycled pulp fibers having the predetermined properties have a carboxyl group amount of 0 to 0.075 mmol / g.
7. The method according to any one of claims 3 to 6, wherein the recycled pulp fibers having the predetermined properties have an increased amount of carboxyl groups of 0 to 0.035 mmol / g based on the pulp fibers.
8. The method according to any one of claims 3 to 7, wherein the recycled pulp fibers having the predetermined properties have a degree of polymerization of 300 or more.
9. The method according to any one of claims 3 to 8, wherein the recycled pulp fibers having the predetermined properties have a reduction in degree of polymerization of 400 or less based on the pulp fibers.
10. The method according to any one of claims 3 to 9, wherein the recycled pulp fibers having the predetermined properties have an alkali solubility of 0 to 20% by mass.
11. The method of any one of claims 3 to 10, wherein the recycled pulp fibers have an increase in alkali solubility of 0 to 16% by weight based on the pulp fibers.
12. The method according to any one of claims 1 to 11, wherein in the recycled pulp fiber forming step, the oxidizing agent and the ultraviolet light are supplied to the aqueous solution in an overlapping manner.
13. The method according to any one of claims 1 to 12, wherein in the recycled pulp fiber forming step, supply of the oxidizing agent to the aqueous solution is started, and then supply of the ultraviolet light to the aqueous solution is started.
14. The method according to any one of claims 1 to 13, wherein in the recycled pulp fiber forming step, the supply of the oxidizing agent to the aqueous solution is stopped, and then the supply of the ultraviolet light to the aqueous solution is stopped.
15. The method according to any one of claims 1 to 14, wherein in the recycled pulp fiber forming step, supply of the ultraviolet light to the aqueous solution is started, and then supply of the oxidizing agent to the aqueous solution is started.
16. The method according to any one of claims 1 to 15, wherein the ultraviolet light comprises ultraviolet light having a wavelength of 380 nm or less.